Textile and dyeing wastewater effectively treated by fenton in moving bed activated carbon system - Nguyen Thai Anh; Nguyen Uy Dong; Huynh Du Triet Quang (Journal of Technical Education Science, 2020)
The complete treatment of colors and hazardous substances at a reasonable cost is of particular interest in the textile industry. In this batch form study, dye solution and textile dyeing wastewater were successfully treated by Fenton technology combining Moving Bed Reactor/Activated carbon (Fenton-MBR/AC) system. The optimum operating conditions including 3.5 of pH value, 0.5 of Fe/H2O2 ratio, 25mL of H2O2 (30%) solution, and 200mL of sample were found. After 60 min, the color removal and efficiency of COD treatment was 94% and 89%, respectively. Besides, the remaining COD after treatment was 97 mg/L. This value meets the requirements for effluent according to the national technical regulations on wastewater quality (QCVN 13:2015/BTNMT). Moreover, the optimal reaction time and the amount of physicochemical sludge generated from this technology were lower than that of traditional Fenton technology. So this technology can be seen as a highly promising technology in textile wastewater treatment in particular and industrial wastewater in general.